Factors Affecting the Use of Internet Banking Services among the Existing Users in Guangzhou, China - Qu, Yulan (2010)
The research is conducted to examine the factors that affect the use of Internet Banking (IB) services among existing IB users in Guangzhou, China. Based on a detailed literature review, research constructs and a proposed model is developed. Questionnaire survey is conducted to collect data and the SPSS 16.0 is employed to test the hypotheses in accordance with the research objectives. Results reveal that perceived security, perceived privacy and perceived compatibility has significant positive effect on IB usage, while perceived ease of use, perceived usefulness and perceived convenience has significant impact. Besides, users’ prior Internet experience has a positive influence on the factors affecting the use of IB, expect the perceived usefulness. Recommendations to IB service provides and discussions for future study are provided.